Diffusion tensor imaging based multiparametric characterization of renal lesions in infants with urinary tract infections: an explorative study - Yvonne Simrén; Eira Stokland; Sverker Hansson; Hanna Hebelka; Par-Arne Svensson; Kerstin M. Lagerstrand (BMC, 2021)
Abstract Background Conventional diffusion weighted imaging (DWI) is a promising non-invasive tool in the evaluation of infants with symptomatic urinary tract infections (UTI). The use of multiparametric diffusion tensor imaging (DTI) provides further information on renal pathology by reflecting renal microstructure. However, its potential to characterize and distinguish between renal lesions, such as acute pyelonephritic lesions, permanent renal damages or dysplastic changes has not been shown. This study aimed to evaluate the potential of multiparametric DTI for characterization of renal lesions with purpose to distinguish acute pyelonephritis from other renal lesions in young infants with their first UTI. Methods Nine kidneys in seven infants, age 1.0-5.6 months, with renal lesions i.e. uptake reductions, on acute scintigraphy performed after their first UTI, were included. The DTI examinations were performed during free breathing without sedation. The signal in the lesions and in normal renal tissue was measured in the following images: b0, b700, apparent diffusion coefficient (ADC), and fractional anisotropy (FA). In addition, DTI tractographies were produced for visibility. Results There was a difference between lesions and normal tissue in b700 signal (197 ± 52 and 164 ± 53, p = 0.011), ADC (1.22 ± 0.11 and 1.45 ± 0.15 mm2/s, p = 0.008), and FA (0.18 ± 0.03 and 0.30 ± 0.10, p = 0.008) for all nine kidneys. Six kidneys had focal lesions with increased b700 signal, decreased ADC and FA indicating acute inflammation. In three patients, the multiparametric characteristics of the lesions were diverging. Conclusion Multiparametric DTI has the potential to further characterize and distinguish acute pyelonephritis from other renal lesions in infants with symptomatic UTI.